موقف الفقه الإسلامي من التعامل مع الأوبئة والجوائح: دراسة فقهية مقارنة - الأكشة، جمال مهدي محمود (جامعة الأزهر - كلية الشريعة والقانون بطنطا, 2021)
يتكون هذا البحث من مقدمة، وتمهيد، وستة مباحث، وخاتمة، وفهارس عامة. وقد انتهيت في هذا البحث إلى ما يلي: 1-أن الوباء مرض عام شديد العدوى، وسريع الانتشار وقد يؤدى إلى الوفاة، كما هو الحال مع وباء كورونا- كوفيد ١٩؛ لذا يجب على ولي الأمر أن يوجه الجهات المختصة بالعمل على الحد من انتشار الوباء، عن طريق وضع حزمة من الاحترازات الوقائية؛ لتجنب إصابة الناس بالوباء والمحافظة على حياتهم؛ لأن حفظ النفس يعد من مقاصد الشريعة الضرورية. 2-وقد حثت الشريعة الإسلامية على المحافظة على النظافة الشخصية، باعتبارها من أهم طرق الوقاية من انتقال الأمراض المعدية، كما أمرت بالتداوي من الأمراض حفاظا على نفس المريض، ولئلا ينتقل المرض إلى غيره من الأصحاء في زمن الوباء. 3-ومن الاحترازات الوقائية في زمن الوباء: منع الاختلاط بين المرضى والأصحاء، وهو ما يسمى (بالحجر الصحي)، كذلك منع المصاب من الخروج من البلدة الموبوءة، ومنع الصحيح من السفر أو الدخول إليها. 4-كما يجب الاحتياط في أداء الفرائض في زمن الوباء، سواء بالنسبة للمريض أو الأطباء المعالجين أو فريق التمريض (أو ما يسمى بالممارس الصحي) وكذلك غيرهم من الأصحاء المخالطين، وذلك في كيفية الطهارة أو أداء الصلاة أو المنع من أدائها بالمسجد أو السماح بأدائها بالمسجد بشروط معينة. 5-كما يجب تقييد الحرية الشخصية في زمن الوباء بما يحقق المصلحة مثل حظر التجوال، وعدم السماح بالسفر إلى البلاد التي ينتشر مها الوباء. 6-كما ينبغي على ولي الأمر أن يوجه الأجهزة المختصة بتوعية جميع أفراد المجتمع عبر وسائل الإعلام ووسائل التواصل الاجتماعي بتجنب نشر الشائعات الكاذبة حول الوباء سواء بالتهويل؛ لإخافة الناس، أو بالتهوين من خطره والتشكيك في وجوده؛ لما يترتب على ذلك كله من آثار سيئة لا يحمد عقباها.
This research consists of an introduction, a preface, six detectives, a conclusion, and general indexes. In this research, I have concluded: 1- The epidemic is a highly contagious, rapidly spreading and potentially fatal general disease, as is the case with the Corona-Covid 19 epidemic; the guardian must therefore direct the competent authorities to work to reduce the spread of the epidemic, by developing a package of preventive precautions to avoid people becoming infected with the epidemic and maintaining their lives; self-preservation is a necessary purpose of sharia. 2- Islamic law has urged the maintenance of personal hygiene, as one of the most important ways to prevent the transmission of infectious diseases, and has ordered medication for diseases to preserve the same patient, lest the disease be transmitted to other healthy people in the time of the epidemic. 3- Preventive precautions in the time of the epidemic include preventing mixing between patients and the healthy, the so-called "quarantine", as well as preventing the infected person from leaving the infested town, and preventing the right person from travelling or entering it. 4- Precautions should also be taken in the performance of petitions in the time of the epidemic, whether for the patient, the treating doctors, the nursing team (or the so-called health practitioner) as well as the unhealthy contacts, in how to purity, perform prayer, prevent it from performing in the mosque or allow it to perform in the mosque on certain conditions. 5- Personal freedom must also be restricted in the time of the epidemic in the interests of such as curfews and travel to countries where the epidemic is spreading must not be allowed. 6- The guardian should also direct the competent agencies to educate all members of society through the media and social media by avoiding spreading false rumours about the epidemic, whether by intimidation, to scare people, to underestimate its danger and to question its existence, all of which have untold ill effects.
Keywords: الفقه الإسلامي -- المقاصد الشرعية -- فيروس كورونا "كوفيد-19" -- النظافة الشخصية